The economics of alternative strategies for the reduction of food-borne diseases in developing countries: The case of diarrhea in Rwanda - Harald von Witzke; Dieter Kirschke; Hermann Lotze-Campen; Steffen Noleppa (Humboldt-Universität zu Berlin, Wirtschafts- und Sozialwissenschaften an der Landwirtschaftlich-Gärtnerischen Fakultät, 2005)
The paper provides a methodology which is suitable for the analysis of the social cost of disease and the benefits and cost of health intervention by integrating public health analysis and economics. The approach developed in the paper is applied to food-borne diarrhea in Rwanda. The results suggest that simple treatments such as Oral Rehydration Therapy have a higher social rate of return than consumer protection via education.
Keywords: I12; I18; Q12; 330; public health; consumer protection; social cost; economics of food-borne diseases